Do Employees Benefit from Worker Representation on Corporate Boards? - Christine Blandhol; Magne Mogstad; Peter Nilsson; Ola Lotherington Vestad (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Do employees benefit from worker representation on corporate boards? Economists and policymakers are keenly interested in this question – especially lately, as worker representation is widely promoted as an important way to ensure the interests and views of the workers. To investigate this question, we apply a variety of research designs to administrative data from Norway. We find that a worker is paid more and faces less earnings risk if she gets a job in a firm with worker representation on the corporate board. However, these gains in wages and declines in earnings risk are not caused by worker representation per se. Instead, the wage premium and reduced earnings risk reflect that firms with worker representation are likely to be larger and unionized, and that larger and unionized firms tend to both pay a premium and provide better insurance to workers against fluctuations in firm performance. Conditional on the firm's size and unionization rate, worker representation has little if any effect. Taken together, these findings suggest that while workers may indeed benefit from being employed in firms with worker representation, they would not benefit from legislation mandating worker representation on corporate boards.
Keywords: G34; G38; J31; J54; J58; 330; worker compensation; worker representation; corporate governance; unions